2012
DOI: 10.5194/acp-12-779-2012
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric aerosol compositions in China: spatial/temporal variability, chemical signature, regional haze distribution and comparisons with global aerosols

Abstract: Abstract. From 2006 to 2007, the daily concentrations of major inorganic water-soluble constituents, mineral aerosol, organic carbon (OC) and elemental carbon (EC) in ambient PM 10 samples were investigated from 16 urban, rural and remote sites in various regions of China, and were compared with global aerosol measurements. A large difference between urban and rural chemical species was found, normally with 1.5 to 2.5 factors higher in urban than in rural sites. Optically-scattering aerosols, such as sulfate (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
290
2
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 749 publications
(317 citation statements)
references
References 92 publications
(95 reference statements)
20
290
2
5
Order By: Relevance
“…The coarse-mode AOD values were just ∼ 0.06 to 0.08, and the ratio of the fine-mode AOD 440 nm to the total AOD 440 nm varies from 0.89 to 0.91 at the sites, and therefore, fine-mode particles clearly were the main contributors to light extinction in the region. The lower coarse-mode fraction of total aerosol extinction (∼ 10 %) indicated that the contribution of coarse particles to aerosol loading in the YRD region is not as obvious as in other northern/northeastern China region (Zhang et al, 2012).…”
Section: Aerosol Optical Properties: Aod and Eaementioning
confidence: 99%
“…The coarse-mode AOD values were just ∼ 0.06 to 0.08, and the ratio of the fine-mode AOD 440 nm to the total AOD 440 nm varies from 0.89 to 0.91 at the sites, and therefore, fine-mode particles clearly were the main contributors to light extinction in the region. The lower coarse-mode fraction of total aerosol extinction (∼ 10 %) indicated that the contribution of coarse particles to aerosol loading in the YRD region is not as obvious as in other northern/northeastern China region (Zhang et al, 2012).…”
Section: Aerosol Optical Properties: Aod and Eaementioning
confidence: 99%
“…Field observations of aerosol particles indicate that they have variable size distributions and can be composed of organic material, inorganic material, or a mixture of both (Shaw and Paur, 1983;Noble and Prather, 1996;Middlebrook et al, 1997;Dusek et al, 2006;Chou et al, 2008;Zhang et al, 2012). Therefore, laboratory studies of aerosol particles are necessary for determining how their various physical and chemical properties affect their ability to act as CCN in the atmosphere.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…This indicates that there were few absorption aerosol particles at the rural site of Shangdianzi and more absorption aerosol particles at both suburban and urban sites during the pollution period. These absorption aerosol particles may consist of black carbon and brown carbon emitted by coal combustion and vehicle exhausts (Zhang et al, 2012;Li et al, 2010). Li et al (2013) found that the proportion of black carbon and brown carbon can reach between 25 and 38 % during pollution events.…”
Section: Inter-comparison Of Aerosol Optical Properties During Pollutmentioning
confidence: 99%